(NgIDROHIMIQ ORO[AEMYH TERRITORIJ (B:s ((NnA PRIMERE BASSEJNA aRALXSKOGO MORQ(B) /s - (N~EMBARISOW(B, (N|LXMIR iSMAILOWI^s ((NtA[KENT (B:s (NfAN(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 101-103s
Keywords: (NaRALXSKOE MORE(B-(NBASSEJNs; (NgIDROHIMIQs; (NoRO[AEMYE POLQ I U^ASTKIs